Education Financing Management During The COVID-19 Pandemic at The Madrasah Tsanawiyah Level: Exploration Of Alternative Solutions - Yuniarto Mudjisusastyo; Agustina Muliati; Rini Ade Octaviany; Winda Sitohang; Rosvina Siburian (STKIP Singkawang, 2023)
The goal of this research is to describe how education funding management was used at the Islamic Junior High School (Madrasah Tsanawiyah/MTsN) level in Medan City during the COVID-19 pandemic, as well as to assess difficulties and potential solutions for education financing during the pandemic. The research method used was descriptive qualitative, with an emphasis on education funding management, and empirical studies were used to address the difficulties. Observation, interviews, and documentation were the three methods used to acquire data for this study. The principal of the Islamic Junior High School (MTsN), namely MTsN 1, MTsN 2, and MTsN 3, Medan City, was the source of information for this study. The findings revealed that education funding management was efficiently implemented during the COVID-19 pandemic. Planning, implementing, coordinating, and supervising operations are all part of the management process, as is giving a solution approach for madrasah principals in managing madrasah funding throughout the pandemic, which has been shown to be successful and ideal. This study is designed to provide an alternate approach for school leaders, administrators, and other stakeholders in terms of managing school finances.